Building codes illustrated a guide to understanding the 2012 international building code - Ching, Frank, 1943- (Building codes illustrated, 2012)
"An easy-to-use, updated illustrated guide to the 2012 edition of the International Building CodeThis unique reference to the 2012 International Building Code marries the graphic skills of bestselling author Frank Ching with the code expertise of Steven Winkel, FAIA. It pulls out the portions of the building code that are most relevant for the architect and provides an easy-to-understand interpretation in both words and illustrations. Rather than a text-heavy book, this is much more conducive to quick comprehension of the code, presenting information in an exciting user-friendly visual format"--